2004
DOI: 10.1159/000080176
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Level, Salivary Flow Rate, and Masticatory Muscle Activity in Response to Acute Mental Stress: A Comparison between Aged and Young Women

Abstract: Background: Age-related effects on physiological stress reactions regarding changes in salivary cortisol concentration, saliva flow rate, and masticatory muscle activity, as well as the corresponding perceived mental stress and performance in response to acute stressors, have not yet been fully described. Objective: Thus, the aim of this study was to assess the age-related variations in these variables in response to minor acute and naturalistic stressors in terms of computer tasks. Methods: 13 aged (60–70 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 35 publications
3
39
0
8
Order By: Relevance
“…In addition to the activation of the forearm muscles, also co-activation of the masseter and temporal muscles has been found during the computer tasks (30). This coactivation has been the most pronounced in elderly participants.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to the activation of the forearm muscles, also co-activation of the masseter and temporal muscles has been found during the computer tasks (30). This coactivation has been the most pronounced in elderly participants.…”
Section: Discussionmentioning
confidence: 85%
“…Of all taste qualities, sour taste induces secretion of the largest volume of saliva by salivary glands (Hodson & Linden, 2006). Increase of saliva flow rate and salivary cortisol concentration has been observed in response to mental stress induced by cognitive activity (Bakke et al, 2004). Acute exposure to stress, such as the one triggered by a cognitive demand or challenge, may act as a mood enhancer and cognitive facilitator (Duncko, Cornwell, Cui, Merikangas, & Grillon, 2007;Sandi & Pinelo-Nava, 2007).…”
Section: Possible Mechanisms Underlying Changes In Cortical Activatiomentioning
confidence: 99%
“…Garde et al (2002) and Wahlström et al (2002) found that blood pressure increased when a mental stressor was added to the computer tasks. Other studies indicated that the cortisol level showed an upward trend after performing stressful tasks such as a two-choice reaction-time test (Nilsen et al 2007) and modiWed Stroop colour-word test (Bakke et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The common typing tasks used in the laboratory studies involved typing of paragraphs of texts (McLean and Urquhart 2002;Johnston et al 2008;Wahlström et al 2002) or typing of numbers with or without mental calculations (Finsen et al 2001;Lundberg et al 2002;Schleifer et al 2008), or both (Hughes et al 2007). The Stroop colour word test is also a common method used to induce mental stress (Bakke et al 2004;Johnston et al 2008;Lundberg et al 2002;), whilst others used a twochoice reaction task for inducing high cognitive demand (Bansevicius et al 1997;Nilsen et al 2007). Recent investigations on mental stress have used a mental arithmetic task Schleifer et al 2008) or task with cognitive (memory) demands (Nilsen et al 2007).…”
Section: Introductionmentioning
confidence: 99%